A Method for the Evaluation of Clinical Information, Exemplified for Bleeding Symptoms in Non-Severe von Willebrand’s Disease Type I - Wahlberg, Th. B. (Methods of Information in Medicine, 1984)
Standardized questions with no- or yes-answers are often used for diagnostic purposes. One common approach is to register only positive answers or confirmation of symptoms, while negative findings are ignored. To illustrate the potential diagnostic value of positive and negative symptoms, twenty-two individuals with von Willebrand’s disease (vWd) type I and 50 non-vWd individuals from three families were investigated. From a self-administered questionnaire, mainly covering bleeding tendency, 19 symptoms were evaluated by a statistical method based on predictive values of negative and positive tests (indicators and predictors). Rank orders of negative findings indicating non-vWd and positive findings indicating vWd were calculated.
Keywords: Medical History; Bleeding Symptoms; Predictive Values; von Willebrand’s Disease